The role of NGOs in corporate environmental responsibility practice: Evidence from Ethiopia - Tibebe Sirak Asfaw; Vida Botes; Lula G. Mengesha (International Journal of Corporate Social Responsibility (JCSR), 2017)
This research explores the role of Non-Government Organizations (NGOs) in corporate environmental responsibility practice within the context of a developing country, Ethiopia, and provides a framework that enables NGOs to influence firms to improve environmental performance and increase environmental disclosure. This research is a qualitative research which employs content analysis. The result of the study shows that the environmental NGOs in Ethiopia are engaged more on reacting to the damage that has been caused by the unsustainable business practices rather than working proactively by collaborating with corporations, government and other stakeholders. This implies that donors should play a pivotal role in this regard since it is the donors' thematic area of activities that dictates the NGOs projects and programs.
Keywords: 650; NGOs; Corporate Environmental Responsibility; Stakeholder; Ethiopia